Vegetation, diversity and rarity on the Cape Peninsula, South Africa - Simmons, Mark T (Plant Conservation Unit (PCU), 2024)
The Cape Peninsula, (471 km2 ) with over 2285 vascular plant species, is characterised by the combination of a diversity of habitats supporting a mosaic of vegetation types. This study attempts describe. and explain some of the determinants of species pattern and distribution. The first part of the thesis compares a simple vegetation classification, derived from visual examination of dominant species and environmental characteristics, • with the results of a multivariate classification derived from the analysis of an extensive database (835 plots, 833 species). This rapid system of classification of fynbos showed an 81 % similarity with Two-Way Analysis (fWA) classification. Detrended Correspondence Analysis (DCA) and Canonical Correspondence Analysis (CCA) were used to relate floristic variation to environmental factors. Theses analyses revealed that altitude, rainfall and soil fertility were the principle environmental factors explaining species distribution. The second part of the thesis examined patterns of local ric~ess and turnover (beta and gamma diversity). Similar sized areas in other mediterranean-climate region biodiversity hot-spots support between 4. 7 and 2. 7 times fewer species than the Cape Peninsula. This high plant regional richness is due to the exceptionally high turnover between moderately species-rich sites in along steep environmental gradients .(beta diversity) and between sites in similar habitats along geographical gradients (gamma diversity). Highest beta diversity, encompassing almost complete turnover, was recorded along soil fertility gradients. Although similar patterns for these independent components explain the richness of other regions in the Cape Floristic region, it is the very long and steep habitat gradients of the Cape Peninsula that makes this region exceptionally rich. Furthermore, the flora is characterized by a high degree of rarity, a phenomenon that undoubtedly influences the turnover. Thus, the third part of this thesis analyses the biological and habitat correlates of plant rarity. Given the Jack of any general theory of University of Cape Town iii ' causality, understanding rarity has become a considerable problem for reserve management. To date, there have been no studies which compare the attributes of rare and ' common plant species. There were no strong relationships between rarity status and biological attributes of species. However, rare species occupy wider resource niches as measured in multivariate space. Although some habitats contained a relatively larger proportion of rare plants, most were riot restricted to particular vegetation types and exhibited ~ wide range of habitat infidelity. However, the distribution of many species, particularly those with high fidelity-indices could be successfully modelled regardless of rarity status abundance. Therefore, although rarity is difficult to predict at the phenomenon level, for management purposes, priority habitats can be identified and the distribution of rare species modelled individually. The results of theses studies are discussed in terms of management and conservation of the Cape Peninsula's uniquely high plant diversity